EXPERIMENTAL STUDY ON MULTIBAND ARROW SHAPE PATCH ANTENNAWITH INVERTED V-SLOT - Ambresh, P A; Sujata, A A; Hadalgi, P M; Hunagund, P V (MATTER: International Journal of Science and Technology, 2015)
A multiband arrow shape patch antenna with inverted V slot (MASPAIVS) is designed and proposed for 3.5 GHz frequency. The antenna is designed with novel inverted wide V-slot and arrow shape patch is fed with a microstripline feed method. The wide inverted V-slot make the antenna to have multiple resonances to operate in the frequency bands of 1 GHz to 13 GHz achieving a maximum impedance bandwidth of 37.38 % in the satellite applications operating band. The antenna shows good return loss characteristics and operates in the L, S, C-Band and military X-band making it suitable for Wi-Max, WLAN and Satellite applications.